PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, LEVERAGE DAN TAX PLANNING TERHADAP MANAJEMEN LABA - Dina Cahyani; Kartika Hendra (Jurnal Akuntansi dan Keuangan, 2020)
This study is to examine and analyze the effect of institutional ownership, company size, leverage and tax planning on earnings management. This study uses SPSS 18, a research instrument for the financial statements of mining companies listed on the IDX with multiple linear regression test research methods. The results show that institutional ownership has a negative effect, while company size, leverage and tax planning have a positive effect on earnings management. The limitations of this study are the lack of samples used and the results of the research are still not good and do not describe the actual market conditions. The benefits of this study are to add insight into earnings management, assist investors in capital issues, assist the government in tax policy to reduce fraud in financial reporting